Pelatihan Strategi Pemasaran Pisang “Sang Mulyo” - Festy Putri Ramadhani; Mumpuni Ningsih, Gumoyo; Bakhtiar, Ary; Muhammad Shodiq, Wahid (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2025)
Purpose –The purpose of this community service activity was to enhance the local community's knowledge and skills in digital marketing, specifically focusing on the marketing of the local banana variety “Sang Mulyo.” By providing training in marketing strategies and the use of digital platforms, this initiative aimed to empower the residents of Sri Mulyo Village to expand their market reach, optimize their product sales, and increase the competitiveness of local micro-enterprises. Additionally, the program sought to support the long-term economic sustainability of the village through the integration of digital marketing solutions. Design/methodology/approach – This research utilized a community engagement-based approach, combining training, mentoring, and simulation methods. The development of online training media was implemented to enhance the digital marketing skills of SMEs in Srimulyo Village, Dampit District, specifically for "Sang Mulyo" banana derivative products. An initial assessment identified local challenges, followed by tailored digital marketing training and marketplace simulation. Continuous mentorship ensured the effective use of marketplace platforms, and participants developed action plans for sustained marketing efforts. Data collection included observation, questionnaires, and interviews, with an evaluation on the impact of digital marketing on product sales and production. Findings –The initial phase began with a preliminary survey of the conditions in Srimulyo Village, Dampit District, focusing on the marketing and product development of "Sang Mulyo" banana derivatives. The team, accompanied by the head of the SriMulyo Farmers Group, identified key issues within the community. Based on these findings, the team formulated training materials. The first phase of the community service activity was conducted on December 20, 2024, at the Srimulyo Village hall. During this phase, basic knowledge about marketplaces, practical application, and step-by-step marketplace creation were introduced. Additionally, platforms like Shopee and Tokopedia were presented as tools for expanding market reach. Originality/value – Overall, the marketing strategy training will have a positive impact on the community. The local population now greatly needs adaptive marketing skills to keep pace with technological advancements. By leveraging digital platforms, the community has a greater opportunity to optimize the sales of their local products in a broader market.